2021
DOI: 10.3390/resources10110109
|View full text |Cite
|
Sign up to set email alerts
|

Urban Vertical Farming as an Example of Nature-Based Solutions Supporting a Healthy Society Living in the Urban Environment

Abstract: The subject of the article concerns vertical urban farms that play an important role in nature-based solutions and ecosystem services for the city. In the face of a changing climate, progressive environmental degradation, and the related loss of agricultural land, vertical farms can be seen as an alternative to traditional agriculture. Woven into the blue-green infrastructure of cities, they may not only constitute a base for food production, but can also create a new valuable ecological, social, and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Among the various forms and technologies of urban agriculture, the vertical garden is a hot topic that was discussed during Covid-19. The benefits of vertical gardening were reviewed at various scales (Zaręba et al, 2021), and it was identified as a technique suitable for integration into design to create a healthy building in the post-Covid-19 era (Navaratnam et al, 2022). At the same time, integration with current innovations and technologies such as automation and the Internet of Things (IoT) was discussed regarding the transformation into smart agriculture (Oh & Lu, 2023;Saad et al, 2021).…”
Section: Innovation and Technologymentioning
confidence: 99%
“…Among the various forms and technologies of urban agriculture, the vertical garden is a hot topic that was discussed during Covid-19. The benefits of vertical gardening were reviewed at various scales (Zaręba et al, 2021), and it was identified as a technique suitable for integration into design to create a healthy building in the post-Covid-19 era (Navaratnam et al, 2022). At the same time, integration with current innovations and technologies such as automation and the Internet of Things (IoT) was discussed regarding the transformation into smart agriculture (Oh & Lu, 2023;Saad et al, 2021).…”
Section: Innovation and Technologymentioning
confidence: 99%
“…Integrating vertical farms into existing urban structures requires compliance with building codes and regulations (Zaręba et al,2021). The design and construction of vertical farming systems must adhere to safety standards, zoning laws, and environmental regulations.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…The installation of smart farms on urban building roofs is attracting attention as a means of dealing with climate and food crises; previous studies have shown promising results [5][6][7][8][12][13][14][15][16][17][18][19]. Because this method utilizes unused rooftop spaces in cities, there is a vast area that can potentially be cultivated, and fresh, locally grown crops can be provided at low prices [5][6][7]13,[20][21][22][23][24][25].…”
Section: Introduction 1study Background and Objectivesmentioning
confidence: 99%